Helicobacter pylori and Metabolic Diseases - Sung Eun Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Helicobacter pylori (H. pylori) is one of the most common pathogens that can cause certain gastrointestinal disorders, such as gastritis, peptic ulcers, and gastric cancer. Recently, interest in the systemic effects of H. pylori on extragastric manifestations is increasing. Representative diseases include hematologic, cardiovascular, neurodegenerative, autoimmune, dermatologic, allergic, hepatobiliary, and metabolic diseases. Among them, since the prevalence of metabolic diseases is on the rise worldwide, the relationship between H. pylori infection and metabolic diseases has become an interesting research issue. Many studies have been conducted to clarify any association. However, the results of those studies still remain controversial. This review focuses on recently published studies to investigate the relationship between H. pylori infection and metabolic diseases, including diabetes mellitus, metabolic syndrome, obesity, and non-alcoholic fatty liver disease, and their associated pathophysiology.